PENGEMBANGAN MODUL PEMBELAJARAN MATERI USAHA DAN ENERGI BERBASIS MASALAH UNTUK KETERAMPILAN BERPIKIR KRITIS - Risa Armika; Stepanus Sahala Sitompul; Syukran Mursyid (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2021)
AbstractThis study aims to find out how to develop a problem-based business and energy material module for critical thinking skills. This type of research is research and development (R&D) using the Borg & gall model. The development of problem-based business and energy material modules for critical thinking skills consists of an introduction cover, a table of contents, an introduction in the form of descriptions, core competencies, basic competencies, indicators, learning objectives and module use, content in the form of concept maps, presentation of problems, material presentation, practice questions, glossary, competency test questions as well as competency test answer keys and the last closing in the form of module identities, and bibliography. The results of data analysis show that the development of problem-based business and energy material modules for critical thinking skills in terms of content feasibility is 83.33% and presentation is 81.11% which is included in the very high criteria. Student responses in the initial field test were 77.49% (high) and 81.49 (very high) in the main field test. So that the results of this study are expected to be a material consideration for schools and teachers in choosing an effective problembased learning module to improve student learning outcomes.Keywords: Development, Learning Module, Effort And Energy